Accelerated long‐term forgetting in focal epilepsy: Do interictal spikes during sleep matter?. (21st January 2021) - Lambert, Isabelle; Tramoni‐Negre, Eve; Lagarde, Stanislas; Pizzo, Francesca; Trebuchon‐Da Fonseca, Agnès; Bartolomei, Fabrice; Felician, Olivier
Abstract: Accelerated long‐term forgetting (ALF) is a particular form of amnesia mostly encountered in focal epilepsy, particularly in temporal lobe epilepsy. This type of memory loss is characterized by an impairment of long‐term consolidation of declarative memory, and its mechanisms remain poorly understood. In particular, the respective contribution of lesion, seizures, interictal epileptic discharges, and sleep is still debated. Here, we provide an overview of the relationships intertwining epilepsy, sleep, and memory consolidation and, based on recent findings from intracranial electroencephalographic recordings, we propose a model of ALF pathophysiology that integrates the differential role of interictal spikes during wakefulness and sleep. This model provides a framework to account for the different timescales at which ALF may occur.